2012
DOI: 10.4172/1948-5948.1000079
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoate Synthesis by Recombinant Escherichia coli JM109 Expressing PHA Biosynthesis Genes from Comamonas sp. EB172

Abstract: Recombinant Escherichia coli JM109 harbouring the polyhydroxyalkanoate (PHA) biosynthesis gene (phaCABco) of Comamonas sp. EB172, an acid tolerant microbe, was examined for the production of PHAs from various carbon sources. The study demonstrated that the recombinant E. coli JM109 had the potential to utilize both sugar-and acid-based carbon sources, for the biosynthesis of both poly(3-hydroxybutyrate) P(3HB) and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) P(3HB-co-3HV) copolymers. In the shake flask experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Alternatively, high PHA-producing strains were engineered to express lactose degradation genes [ 57 ]. Recombinant E. coli has commonly been employed for PHA production due to its convenience for genetic manipulation, fast growth, high cell density cultivation, and its ability to utilize inexpensive carbon sources [ 58 ]. Therefore, the development of recombinant E. coli will be one of the applicable methods to improve PHA production.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, high PHA-producing strains were engineered to express lactose degradation genes [ 57 ]. Recombinant E. coli has commonly been employed for PHA production due to its convenience for genetic manipulation, fast growth, high cell density cultivation, and its ability to utilize inexpensive carbon sources [ 58 ]. Therefore, the development of recombinant E. coli will be one of the applicable methods to improve PHA production.…”
Section: Resultsmentioning
confidence: 99%
“…Different agricultural wastes can be used for this purpose through chemical or enzymatic hydrolysis (Du et al 2012;Sandhya et al 2013). Mono-and disaccharides can be used for the production of PHAs mainly in aseptic cultivation because it is possible to select strains of bacteria (Du et al 2012;Vishnuvardhan and Thirumala 2012;Yee et al 2012) or yeasts (Abd-El-Haleem et al 2007) with low production of storage carbohydrates under excess of carbon and energy source. Meanwhile, the wild strains of microorganisms in non-aseptic mixed culture will transform excess of external sugars to the glycogen, exopolysaccharides, or lipids (Ivanov 2010).…”
Section: Problems Of Pha Productionmentioning
confidence: 99%
“…These bacteria can utilize urea as a sole nitrogen source for its growth and has the ability to hydrolyze urea to ammonia [31]. Ye et al (2012) reported 37% production of PHA using mixed volatile fatty acids recombinant Escherichia coli [32].…”
Section: Pha Production From Volatile Fatty Acidsmentioning
confidence: 99%